Experimental investigation on reparability of an infilled rocking wall frame structure. (20th June 2017) - Wu, Shoujun; Pan, Peng; Nie, Xin; Wang, Haishen; Shen, Shaodong
Summary: Improving seismic performance is one of the critical objectives in earthquake engineering. With the development of economy and society, reparability and fast resilience of a structure are becoming increasingly important. Reinforced concrete (RC) frame structure is prone to soft story mechanism. As a result, deformation and damage are so concentrated that reparability is severely hampered. Rocking wall provides an available approach for deformation control in RC frame by introducing a continuous component along the height. Previous researches mostly focus on seismic responses of rocking wall frame structures, while damage mode and reparability have not been investigated in detail. In this study, a novel infilled rocking wall frame (IRWF) structure is proposed. A half‐scaled IRWF model was designed according to Chinese seismic design code. The model was subjected to cyclic pushover testing up to structure drift ratio of 1/50 (amplitude 1/50), and its reparability was evaluated thereafter. Retrofit was implemented by wrapping steel plates and installing friction dampers. The retrofitted model was further loaded up to amplitude 1/30. The IRWF model showed excellent reparability and satisfactory seismic performance on deformation control, damage mode, hysteresis behavior, and beam‐to‐column joint rotation. After retrofitting, capacity of the model was improved by 11% with limited crack distribution. The model did not degrade until amplitude 1/30, due to shear failure in frame beams. The retrofit procedure was proved effective, and reparability of the IRWF model was demonstrated. Seismic resilience tends to be achieved in the proposed system.